Species-specific Bioactivation of Morpholines as a Causative of Drug Induced Liver Injury Observed in Monkeys - Gunduz, Mithat; Argikar, Upendra A.; Cirello, Amanda L.; Brown, Alan P.; Bonazzi, Simone; Walles, Markus (Drug Metabolism and Bioanalysis Letters, 2024)
Background: Everolimus, an allosteric mechanistic target of rapamycin (mTOR) inhibitor, recently demonstrated the therapeutic value of mTOR inhibitors for Central Nervous System (CNS) indications driven by hyperactivation of mTOR. A newer, potent brain-penetrant analog of everolimus, referred to as (1) in this manuscript [(S)-3-methyl-4-(7-((R)-3-methylmorpholino)-2- (thiazol-4-yl)-3H-imidazo[4,5-b]pyridin-5-yl)morpholine,(1)] catalytically inhibits mTOR function in the brain and increases the lifespan of mice with neuronal mTOR hyperactivation. Introduction: Early evaluation of the safety of 1 was conducted in cynomolgus monkeys in which oral doses were administered to three animals in a rising-dose fashion (from 2 to 30 mg/kg/day). 1 produced severe toxicity including the evidence of hepatic toxicity, along with non-dose proportional increases in drug exposure. Investigations of cross-species hepatic bioactivation of 1 were conducted to assess whether the formation of reactive drug metabolites was associated with the mechanism of liver toxicity. Methods: 1 contained two morpholine rings known as structural alerts and can potentially form reactive intermediates through oxidative metabolism. Bioactivation of 1 was investigated in rat, human and monkey liver microsomes fortified with trapping agents such as methoxylamine or potassium cyanide. Results: Our results suggest that bioactivation of the morpholine moieties to reactive intermediates may have been involved in the mechanism of liver toxicity observed with 1. Aldehyde intermediates trappable by methoxylamine were identified in rat and monkey liver microsomal studies. In addition, a total of four cyano conjugates arising from the formation of iminium ion intermediates were observed and identified. These findings may potentially explain the observed monkey toxicity. Interestingly, methoxylamine or cyano adducts of 1 were not observed in human liver microsomes. Conclusion: The bioactivation of 1 appears to be species-specific. Circumstantial evidence for the toxicity derived from 1 point to the formation of iminium ion intermediates trappable by cyanide in monkey liver microsomes. The cyano conjugates were only observed in monkey liver microsomes, potentially pointing to cause at least the hepatotoxicity observed in monkeys. In contrast, methoxylamine conjugates were detected in both rat and monkey liver microsomes, with only a trace amount in human liver microsomes. Cyano conjugates were not observed in human liver microsomes, challenging the team on the drugability and progressivity of 1 through drug development. The mechanisms for drug-induced liver toxicity are multifactorial. These results are highly suggestive that the iminium ion may be an important component in the mechanism of liver toxicity 1 observed in the monkey.
Keywords: liver microsomes